Pengaruh Profitabilitas, Solvabilitas Dan Corporate Social Responsibility (CSR) Terhadap Manajemen Laba: Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2020-2022 - Alika Putri (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2025)
The problem in this study is that there are still several cases of earnings management carried out by manufacturing companies that cause losses to shareholders and the company itself. This study aims to determine the effect of Profitability, Solvency and Corporate Social Responsibility (CSR) on earnings management in manufacturing companies listed on the IDX in 2020-2022 partially and simultaneously. The population in this research is all manufacturing companies listed on the IDX for the 2020-2022 period. Sample selection used the purposive sampling method. Based on predetermined criteria, a sample of 54 companies was obtained, with three years of observation so that the observation data amounted to 162 observations. The data analysis technique used is multiple regression assisted by SPSS 26. The results of this research indicate that profitability has a partial effect on earnings management. Solvency partially influences earnings management. corporate social responsibility has no partial effect on earnings management. Profitability, solvency and corporate social responsibility simultaneously influence earnings management. The conclusion of this research is that profitability and solvency have a positive and significant effect on earnings management. corporate social responsibility has a negative and significant effect on earnings management. Meanwhile simultaneously profitability, solvency and corporate social responsibility on earnings management have a positive and significant effect on earnings management.